Perceived corporate entrepreneurship in GLCs: evidence from Malaysia - Entebang, Harry; Ernest Cyril , de Run; Harrison, Richard T. (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to gauge the extent to which government‐linked companies in Malaysia demonstrate corporate entrepreneurship activities.